Differentiating Slowly Progressive Subtype of Lower Limb Onset ALS From Typical ALS Depends on the Time of Disease Progression and Phenotype - Zhang, Huagang; Chen, Lu; Tian, Jinzhou; Fan, Dongsheng (Frontiers in Neurology, 2022)
Background: Flail leg syndrome (FLS) is a regional variant of amyotrophic lateral sclerosis (ALS) with the characteristics of slow progression and symptoms confined to the lumbosacral region for extended periods. However, FLS may not be easily differentiated from typical ALS. Objective: The objective of the study was to determine a cutoff time of disease progression that could differentiate FLS from typical lower limb onset ALS well. Methods: A cutoff point analysis was performed with maximally selected log-rank statistics in lower limb onset ALS patients registered from 2009 to 2013. Based on the cutoff duration from lower limb onset to second region significantly involved (SRSI), all patients were divided into the slowly progressive subtype of lower limb onset ALS group and the typical lower limb onset ALS group. Patients with slowly progressive subtype of lower limb onset ALS, who had the flail leg phenotype, were classified as FLS patients. Differences between groups were analyzed. Results: Of 196 patients recruited, 157 patients with a duration<14 months from lower limb onset to SRSI were classified as having typical lower limb onset ALS. Twenty-nine patients with a duration≥ 14 months and the flail leg phenotype were classified as having FLS. FLS patients exhibited a median diagnostic delay of 25 months, a median duration of 24 months from lower limb onset to SRSI, an forced vital capacity (FVC) abnormity rate of 12.5% at the first visit in our department, and a median survival time of 80 months, which were significantly different from those of typical lower limb onset ALS patients (P<0.001, P<0.001, P=0.024, P<0.001). The 5-year survival rate of the FLS group (79.3%) was much higher than that of the other group (1.9%). Conclusions: A crucial feature in differentiating FLS from typical lower limb onset ALS in Chinese patients may be symptoms confined to the lumbosacral region for at least 14 months, which may be better than 12 or 24 months used in previous studies. FLS was characterized by slower progression, less and later respiratory dysfunction and a more benign prognosis than typical lower limb onset ALS.